Studi Etnografi Budaya Sekolah Dalam Membentuk Karakter Religius Di Sekolah Dasar Negeri Bajangan Gondang Wetan Pasuruan - Himmatul Ulya; Ahmad Marzuki (4, 2024)
Moral education, or better known as character education, is a series of basic moral principles and the virtues of attitude and character or nature that must be possessed and made a habit by children from the beginning until they become mukallaf, that is, ready to navigate the sea of ​​life. Imam al-Ghazali emphasized that morality is a trait embedded in the human soul, which can be judged good or bad using the standards of science and religious norms. Character education has a very important role in shaping the personality of Indonesian people who have the integrity of their Indonesian soul. This study aims to examine how school culture at Bajangan Gondang Wetan Pasuruan Elementary School shapes the religious character of students. The method used in this study is an ethnographic study, which allows researchers to explore in depth the cultural practices that exist in the school and their influence on the formation of students' religious character. This study uses a qualitative approach with data collection through participatory observation, in-depth interviews, and document analysis. The results of the study indicate that the school culture at SDN Bajangan is strongly influenced by religious values, which are reflected in various aspects of school life, such as habituation activities, school regulations, and social interactions between teachers, students, and parents. Habituation activities such as praying together before starting lessons, weekly religious activities, and commemorating religious holidays play a significant role in instilling religious values ​​in students. Furthermore, the attitudes and behavior of teachers as role models in implementing religious values ​​also significantly influence the formation of students' religious character. Harmonious social interactions and mutual respect among school members contribute to strengthening an environment conducive to the development of religious character. Abstrak Pendidikan akhlak atau yang lebih dikenal dengan karakter adalah serangkain prinsip dasar moral dan keutamaan sikap serta watak atau tabiat yang harus dimiliki dan dijadikan kebiasaan oleh anak sejak masa pemula hingga menjadi mukallaf, yakni siap untuk memengarungi lautan kehidupan. Imam al-Ghazali menekankan bahwa akhlak adalah sifat yang tertanam dalam jiwa manusia, yang dapat dinilai baik atau buruk dengan menggunakan ukuran ilmu pengetahuan dan norma agama Pendidikan karakter memiliki peran yang sangat penting dalam membentuk pribadi manusia Indonesia yang memiliki keutuhan jiwa ke-Indonesiannya. Penelitian ini bertujuan untuk mengkaji bagaimana budaya sekolah di Sekolah Dasar Negeri Bajangan Gondang Wetan Pasuruan membentuk karakter religius siswa. Metode yang digunakan dalam penelitian ini adalah studi etnografi, yang memungkinkan peneliti untuk menggali secara mendalam praktik budaya yang ada di sekolah serta pengaruhnya terhadap pembentukan karakter religius siswa. Studi ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui observasi partisipatif, wawancara mendalam, dan analisis dokumen. Hasil penelitian menunjukkan bahwa budaya sekolah di SDN Bajangan sangat dipengaruhi oleh nilai-nilai religius yang tercermin dalam berbagai aspek kehidupan sekolah, seperti kegiatan pembiasaan, tata tertib sekolah, dan interaksi sosial antara guru, siswa, dan orang tua. Kegiatan pembiasaan seperti doa bersama sebelum memulai pelajaran, kegiatan keagamaan mingguan, dan peringatan hari-hari besar agama memiliki peran signifikan dalam menanamkan nilai-nilai religius kepada siswa. Selain itu, sikap dan perilaku guru sebagai teladan dalam menerapkan nilai-nilai religius juga sangat berpengaruh terhadap pembentukan karakter religius siswa. Interaksi sosial yang harmonis dan saling menghargai antarwarga sekolah turut memperkuat lingkungan yang kondusif bagi pengembangan karakter religius.